Repercussões da incontinência urinária sobre a satisfação sexual de mulheres: um estudo qualitativo - Britto, Debora Fernandes (2020)
Despite the great interest of researchers on sexual life of incontinent women and, recently, on sexual satisfaction as a dimension of sexuality, there are few studies to determine which issues are important from their own point of view. The aim of this study was to explore the perceptions of these women about the repercussions of urinary incontinence (UI) on sexual satisfaction. It was a qualitative study. Semi-structured face-to-face interviews with 88 women with UI, aged between 32 and 79 years, with different marital status, occupations and education, reaching the saturation of the data. The research was conducted in two health centers in Brazil, from 2016 to 2017. Semi-structured interviews addressed topics such as the importance of sex, how they would like to live their sex life and how UI interfered with their sexual relations. The interviews were transcribed and analyzed according to the thematic content analysis by Bardin's technique. From that, thematic unit were emerged which were grouped in three thematic categories: 1- interface between sex importance and relations aspects; 2- expectations and wishes about sexual life; and 3- challenges and strategies in conciliation between sexual life and UI. It is possible to understand that UI has influence to the women’s sexual life who have active and not active sexual life. It happens direct and indirect ways in the sexual life. Directly, women point out that the experience of sexuality is affected by the symptoms of urine odor, contraction of the pelvic floor or urinary loss at the time of intimacy. In the indirect way, the sexual satisfaction in a relationship permeated by struggles related to the routine, the low quality of communication was damaged. It was comprehended that despite the UI condition, is in the relation dimension where there are the biggest difficulties related to the sexual life.